LARIS: a local-state active reasoning and integrated switching framework for robotic harvesting under partial observability - Nianzu Dai; Jiaming Fang; Jin Yuan; Xuemei Liu (Computers and Electronics in Agriculture, 2026)

Synergistic architecture and dynamic adaptability in heterogeneous catalysts for CO2 hydrogenation - Jiao Liu; Xingyi Cen; Jiaming Lin; Junrong Yue; Duo Sun; Fang Wang (Journal of Environmental Sciences, 2026)

Transcriptomics analyses reveal microgravity triggers estrogen synthesis amidst degeneration and aging in human ovarian granulosa cells - Changjian Yin; Jiaming Zhang; Zihang Cheng; Fang He; Haiquan Lu; Shigang Zhao (Life Sciences in Space Research, 2026)

Unlocking ultrahigh anion adsorption in sunlight-responsive metal-organic frameworks for water purification - Xu Wu; Qian Guan; Mengyu Tang; Yilei Fang; Jiaming Gan; Xinyu Zhang; Xin Yu; Ranwen Ou (Chemical Engineering Journal, 2026)

Phenytoin quaternary ammonium salt is a novel wound treatment drug with both pro-healing and antibacterial effects - Yuchen Li; Jiaming Cui; Peihui Zhou; Bixuan Cao; Li Zhao; Weize Kong; Xueheng Sun; Ya Fang; Jinwu Wang; Mingzhi Song; Li Wang (Chemical Engineering Journal, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

Numerical Simulation of an Icebreaker Ramming the Ice Ridge - Wenbo Dong; Jiaming Chen; Yufei Zhang; Shisong Wei; Guangwei He; Fang Li (Journal of Marine Science and Engineering, 2025)
During polar navigation, icebreakers frequently encounter ice ridges, which can significantly reduce navigation efficiency and even pose threats to structural safety. Therefore, studying the ramming of ice ridges by the icebreaker is of great importance. In this study, the ice ridge is decoupled into the consolidated layer and the keel for modeling. The consolidated layer is simplified as layered ice, and an innovative hybrid empirical–numerical method is used to determine the icebreaking loads. For the keel, a failure model is developed using the Mohr–Coulomb criterion in combination with the effective stress principle, accounting for shear failure in porous media and incorporating both cohesion and internal friction angle. The ship is restricted to surge motion only. A comparative analysis with the model test results was conducted to assess the accuracy of the method, with the predicted ice resistance showing deviation of 9.85% in the consolidated ice area and 10.48% in the keel area. Ablation studies were conducted to investigate the effects of different ice ridge shapes, varying retreat distances, and different ship drafts on the performance of ramming the ice ridge. The proposed method can quickly and accurately calculate ice ridge loads and predict their motion responses, providing a suitable tool for on-site rapid navigability assessment and for the design of icebreakers.

Investigation on hydraulic conductivity reduction for silty sand by enzyme induced calcium carbonate precipitation considering urease activity and cementing solution concentration - Lei Shi; Liuhui Huo; Jiaming Fang; Xiangchun Xu; Jianwei Zhang (Engineering Geology, 2025)

Ceramic ultrafiltration membrane as pretreatment for drinking water nanofiltration treatment: Performance, cleaning, and costs based on an engineering case - Yawei Xie; Chengyue Fan; Yichen Fang; Xiwang Zhu; Jiaming Yan; Haodong Liu; Hongyuan Liu (Journal of Cleaner Production, 2025)

Design and interaction dynamics analysis of a novel hybrid bending-twisting-pulling end-effector for robotic tomato picking - Jiaming Fang; Nianzu Dai; Zhenbo Xin; Jin Yuan; Xuemei Liu (Computers and Electronics in Agriculture, 2025)

Multi-omics revealed activation of TNF-α induced apoptosis signaling pathway in testis of DEHP treated prepubertal male rat - Zishui Fang; Zirun Jin; Qiancheng Zhao; Jiaming Weng; Zhe Zhang; Yuzhuo Yang; Hui Jiang (Reproductive Toxicology, 2025)

pLM33 provides tolerance of persistent Listeria monocytogenes ST5 to various stress conditions and also enhances its virulence - Xin Liu; Tianqi Shi; Jiaming Li; Huanyu Wu; Qing Zhao; Zhixin Fang; Yingying Liang; Quan Xiao; Min Chen; Qingli Dong; Hongzhi Zhang (Food Microbiology, 2025)

The impact of short-term exposure to criteria air pollutants on sleep disturbance among young adults: A nationwide analysis in 261 Chinese cities - Chunliang Wang; Kai Su; Linming Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Jiaming Liu; Junteng Zhou; Chenyu Xu; Hualu Gan; Lingyan Chen; et al. (Environmental Research, 2025)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

3MSP2: Sequential picking planning for multi-fruit congregated tomato harvesting in multi-clusters environment based on multi-views - Nianzu Dai; Jiaming Fang; Jin Yuan; Xuemei Liu (Computers and Electronics in Agriculture, 2024)

Suspended sediment-discharge hysteresis characteristics and controlling factors in a small watershed of southern China - Yu Long; Ming Lei; Taoxi Li; Peiyao Xiao; Siyuan Liu; Jiaming Xu; Fang Tang; Xuexiang Hu; Xizhong Hu; Xiaodong Nie; Zhongwu Li; Yaojun Liu (CATENA, 2024)

Fabrication of hyaluronic acid-altered gold complex delivery for head and neck squamous cell carcinoma therapy with high antitumor efficacy and low in vivo toxicity - Shizhi He; Jiaming Chen; Yanming Zhao; Ru Wang; Yurong He; Shaoshi Chen; Yifan Yang; Changyu Zhu; Jingyang Zhao; Jugao Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Using geodetic measurements derived terrestrial water storage to investigate the characteristics of drought in Yunnan, China - Chao Chen; Rong Zou; Zhiwei Fang; Jiaming Cao; Qi Wang (GPS Solutions, 2024)
The use of the global navigation satellite system (GNSS) for monitoring changes in terrestrial water storage (TWS) is growing. However, the density of GNSS stations is sparse in most areas, and the widely used Green’s function (GF) method cannot provide a satisfactory resolution for inversion problems. As the Slepian basis function (SBF) method has been successfully used for gravity inversions, GNSS geodesists have recently applied the SBF method to GNSS displacements. However, the evaluation of TWS differences inferred from GNSS using the SBF and the GF has been rarely assessed. In this study, we use both the GF and the SBF methods to investigate the TWS in Yunnan by using more than ten years (2010–2021) of GNSS observations. We observe a remarkable consistency between the two inversion methods employed for GNSS data, as well as a strong agreement with equivalent water heights (EWH) inferred from the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow-On (GFO), hydrological model (GLDAS-NOAH), and precipitation data, despite variations in the amplitude. Furthermore, affected by monsoon climate and topography, Yunnan is prone to drought. We analyze the main nine drought events, evaluate the connection between GNSS-inverted TWS during 2010–2021, and find that almost all droughts in Yunnan occurred during the "trough period" within the GNSS-DSI.

Role of mining waste trade on green development in China: Policy implications for circular economy - Siming Yu; Xun Wang; Jiaming Liu; Fang Wei (Resources Policy, 2023)

Extreme low-temperature events can alleviate micronutrient deficiencies while increasing potential health risks from heavy metals in rice - Min Kang; Xue Wang; Jiankun Chen; Qizhao Fang; Jiaming Liu; Liang Tang; Leilei Liu; Weixing Cao; Yan Zhu; Bing Liu (Environmental Pollution, 2023)

Quality retention and delay postharvest senescence of figs (Ficus carica L.) using 1-methylcyclopropene and modified atmosphere packaging during cold storage - Cailian Wang; Jiaming Du; Dehua Hou; Xiaohong Guo; Qianting Liu; Linwen Liu; Yu Fang; Liping Kou (Food Bioscience, 2023)

The role of the joint capsule in the stability of the elbow joint - Fang Wang; Hao Wang; Mingxin Li; Shuoqi Jia; Jiaming Wang; Jianguo Zhang; Yubo Fan (Medical & Biological Engineering & Computing, 2023)

Dynamic response of single-bucket foundation in clay under vertical variable amplitude cyclic loadings - Hailei Kou; Weiwei Fang; Nan Zhou; Jiaming Huang; Xixin Zhang (Ocean Engineering, 2023)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.

Study on mechanical properties and elasto-brittle-plastic constitutive model of hard brittle rock based on conventional triaxial test - Xinxin Fang; Han Tong; Jiaming Feng; Yanqiu Wang; Xiaowei Ni; Shaoyong Hou; Kang Bie (Arabian Journal of Geosciences, 2022)

Role of rgsA in Oxidative Stress Resistance in Pseudomonas aeruginosa - Shuyi Hou; Jiaqin Zhang; Xiaobo Ma; Qiang Hong; Lili Fang; Gangsen Zheng; Jiaming Huang; Yingchun Gao; Qiaoli Xu; Xinguo Zhuang; Xiuyu Song (Current Microbiology, 2021)

A conjugated mTOR/MEK bifunctional inhibitor as potential polypharmacological anticancer agent: the prototype compound discovery - Qiangqiang Tao; Fang Fang; Jiaming Li; Yong Wang; Can Zhao; Jingtai Liang; Xiaodong Ma; Hao Wang (Medicinal Chemistry Research, 2020)

Expression and Selection of Human Foxm1c Binding Peptides and Their Inhibitions on MCF7 Cancer Cells - Jian Cui; Jiaming Huang; Tailin Guo; Fang Wu; Zhijuan Liang; Lili Xiong; Tingting Huang; Li Zeng; Na Liu; Canquan Mao (International Journal of Peptide Research and Therapeutics, 2014)

Clinical Analysis of 15 Cases of Liver Nodular Regenerative Hyperplasia - Tao Guo; Jiaming Qian; Liming Zhu; Weixun Zhou; Feng Zhu; Gang Sun; Xiucai Fang (Cell Biochemistry and Biophysics, 2012)

AtRabD2b, a Functional Ortholog of the Yeast Ypt1, Controls Various Growth and Developmental Processes in Arabidopsis - Fang Wang; Chao Liu; Chen Wei; Yuhai Cui; Qian Zheng; Jiaming Zhang; Jiangsheng Wu; Kede Liu (Plant Molecular Biology Reporter, 2012)